(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article provides a comparative linguistic analysis of the semantic field of educational and pedagogical terms as well as their structural-semantic features in English and Uzbek. The study examines the formation of pedagogical terminology, semantic expansion and narrowing, and the functional scope of usage. It identifies the degree of correspondence between English and Uzbek terms, issues of equivalence, and semantic differences shaped by national and cultural factors. The structural composition of terms — simple, compound, and phraseological units — is also analyzed to determine their role in academic discourse. The findings of the research contribute to the systematization of pedagogical terminology, improvement of translation practices, and development of scientific communication in the field of education.